2022
DOI: 10.3390/polym14101954
|View full text |Cite
|
Sign up to set email alerts
|

Development of Geopolymers Based on Fly Ashes from Different Combustion Processes

Abstract: The main aim of this research is to assess different fly ashes as raw materials for the manufacturing of geopolymers. Three different fly ashes have been investigated. First, a conventional fly ash from the Skawina coal power plant (Poland), obtained at a temperature of 900–1100 °C. Second, ultra-fine fly ash from a power plant in China; the side product received at 1300 °C. The third fly ash was waste was obtained after combustion in incineration plants. To predict the properties and suitability of materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Compared with ordinary Portland cement, geopolymers have excellent properties such as acid resistance, alkali resistance, impermeability, frost resistance and high-temperature resistance [ 19 , 20 , 21 , 22 ]. However, since the hydration products of geopolymers do not contain Ca(OH) 2 as a buffer, their carbonation resistance is much lower than that of ordinary silicate concrete [ 23 , 24 ]. The carbonization resistance of geopolymer is a key factor affecting its durability and is an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ordinary Portland cement, geopolymers have excellent properties such as acid resistance, alkali resistance, impermeability, frost resistance and high-temperature resistance [ 19 , 20 , 21 , 22 ]. However, since the hydration products of geopolymers do not contain Ca(OH) 2 as a buffer, their carbonation resistance is much lower than that of ordinary silicate concrete [ 23 , 24 ]. The carbonization resistance of geopolymer is a key factor affecting its durability and is an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…As a common precursor of geopolymer material, the compressive strength of geopolymers formed from different types of fly ash is related to the variation of fly ash in particle size distribution, chemical composition, morphological properties and amorphous phase [ 10 ]. It has been shown that the geopolymer made from ultrafine fly ash has a higher compressive strength than conventional fly ash, but the flexural strength is only one-twentieth of that of conventional fly ash geopolymer [ 11 ]. In addition, calcium in fly ash can promote the formation of C-S-H gels, and fly ash with high calcium content is more conducive to improving the strength of geopolymer [ 12 ], but the inadequacy of calcium fraction on the development of three-dimensional mesh structure of geopolymer restricts the application of high-calcium fly ash [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cement serves as a concrete binder and creates stunning structures for human civilization, and simultaneously, its production process emits a large amount of CO 2 [ 1 , 2 , 3 ]. Cement production accounts for about 7% of the world’s CO 2 emissions [ 4 ]. In addition, 1700 kg of raw materials are consumed to make 1000 kg of clinker [ 5 ].…”
Section: Introductionmentioning
confidence: 99%